Tourism Development Through Creative Economy in Saudi Arabia: Sustaining Coffee as A Culinary Destination in Buraidah - Maspul, Kurniawan Arif (DAS Institute, 2022)
Ideas and community synergy are required in maintaining a creative economy in strengthening not only the local economy but likewise being a role in its development of coffee productivity, profitability and quality growth in the Middle East's coffee value chain to the global level. Visiting the development of specialty coffee in Saudi Arabia in recent years has made it one of the options for the creative economy built on community development in local tourism growth. Critically in Buraidah as one of the UNESCO Creative Cities Network (UCCN) in the field of gastronomy, specialty coffee is entirely resonant with its synergies around the coffee value chain in Saudi Arabia, making it one of the proponents of the local creative economy. This paper is a qualitative descriptive through the literature, observations, site visits and interviews, which were analysed, concluded that the creative economy through coffee in Buraidah has developed more profoundly in strengthening the sustainable economy as a culinary destination in the region. All actors from the coffee value chain in the region are anticipated to be able to sustain its development for a better future generation.